Global research and emerging trends in depression in lung cancer: a bibliometric and visualized study from 2014 to 2024 - Lin, Weilan; Chen, Shun; Chen, Jiawei; Wang, Chune; Lu, Feng (Frontiers in Oncology, 2025)
BackgroundThe impact of depression on the physical and psychological well-being of lung cancer patients has raised significant concerns. This study explored lung cancer-related depression research from a bibliometric perspective.MethodsArticles and reviews on depression in lung cancer published from 2014 to 2024 in the Web of Science Core Collection were retrieved and identified. The information extracted included “Full Record and Cited References”. Bibliometric analysis was conducted using CiteSpace and Excel to examine relevant publications in terms of country, institution, authorship, journal, citations, and keywords.ResultsA total of 761 publications on depression in lung cancer were identified for analysis, contributed by 4,667 authors from 305 institutions and 58 countries. The annual publication count has steadily increased, culminating in a peak in 2024. China (275 papers), Harvard University (58 publications), and Joseph A. Greer (25 publications) were the most productive and influential country, institution, and author, respectively. Jennifer S. Temel emerges as a highly influential author, securing the second position in terms of both publication count and citation impact. The journal with the highest number of publications is Supportive care in cancer, while the Journal of Clinical Oncology has garnered the most citations. Reference and keyword analysis indicated that the research hotspots mainly included 1) Epidemiology of lung cancer-related depression; 2) The deleterious impact of depression on lung cancer patients, particularly with regards to their quality of life; 3) Association between inflammation and depression in lung cancer; 4) Treatment.ConclusionsOur study employed bibliometric analysis to identify prevalent focal areas and emerging trends in the field of research on lung cancer-related depression. Our study found that numerous unanswered questions persist, including the intricate relationship between lung cancer and depression, the profound impact of depression on lung cancer patients, and the interplay between inflammation and depression in this specific population. Furthermore, a current challenge in clinical practice involves the development of secure and more efficacious treatment strategies for individuals with lung cancer-related depression. These findings provide valuable guidance for scholars seeking to explore new avenues of investigation.